Saving in India, 1950-51 to 1961-62 - National Council of Applied Economic Research (New Delhi : National Council of Applied Economic Research, 1965)
The book contains a revision of the earlier aggregates estimates of the total net national saving in India and aims at providing from the available basic data the saving and investment figures for the latest possible year.
Includes bibliographical footnotes.
usc 31/10/18
Loans
Keywords: Saving and investment; India